2002
DOI: 10.1111/j.1572-0241.2002.05993.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in patients with liver disease

Abstract: CAM use is as common among patients visiting liver disease clinics in the United States as in the general population (39% vs 42%). Many patients are using herbs to treat their liver disease but are declining to discuss this use with their physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
5
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 12 publications
5
78
5
3
Order By: Relevance
“…20 Milk thistle, the active ingredient of which is silybum marianum, is the most commonly used herbal among liver disease patients. 21 Silybum has hepatoprotective effects in animal models of liver disease, specifically preventing the formation of superoxide anions, nitric oxide, tumor necrosis factor (TNF)-␣, and leukotriene B4. [22][23][24] In clinical studies, milk thistle, glycyrrhiza glabra (licorice) and sho-saiko-to (a Japanese Kampo formula consisting of 7 different herbals) have been reported to decrease ALT levels, improve histological stage, and improve symptoms in patients with several liver diseases.…”
Section: Management Of the Difficult-to-treat Patients With Hepatitis Cmentioning
confidence: 99%
“…20 Milk thistle, the active ingredient of which is silybum marianum, is the most commonly used herbal among liver disease patients. 21 Silybum has hepatoprotective effects in animal models of liver disease, specifically preventing the formation of superoxide anions, nitric oxide, tumor necrosis factor (TNF)-␣, and leukotriene B4. [22][23][24] In clinical studies, milk thistle, glycyrrhiza glabra (licorice) and sho-saiko-to (a Japanese Kampo formula consisting of 7 different herbals) have been reported to decrease ALT levels, improve histological stage, and improve symptoms in patients with several liver diseases.…”
Section: Management Of the Difficult-to-treat Patients With Hepatitis Cmentioning
confidence: 99%
“…Among 809 patients who completed the questionnaire, 41% (range 33% to 75% at the 6 institutions) indicated that they had used some form of CAM at least once during the preceding month. 5 Herbal preparations were taken by 12% to 50% (median, 20%) of patients. The most common herbal taken for liver disease was milk thistle (silymarin), reported by 12% of respondents.…”
Section: Use Of Cam By Patients In Liver Disease Clinicsmentioning
confidence: 99%
“…Thus, there are many patients who have no other Food and Drug Administration-approved options to eliminate HCV and prevent progression of liver disease. As a result, many individuals have opted for complementary and alternative medicine-based approaches, including botanicals, to treat their chronic hepatitis C. Indeed, as many as 13 to 23% of American patients with chronic liver disease use botanical medicines, with silymarin being the most popular (6,7).…”
mentioning
confidence: 99%